2017
DOI: 10.1021/acs.jpcb.7b01289
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Serum Albumin Fibrillation by Two-Dimensional Nanoparticles

Abstract: The formation and deposition of amyloid fibrils have been linked to the pathogenesis of numerous debilitating neurodegenerative disorders. Serum albumins serve as good model proteins for understanding the molecular mechanisms of protein aggregation and fibril formation. Graphene-based nanotherapeutics appear to be promising candidates for designing inhibitors of protein fibrillation. The inhibitory effect of graphene oxide (GO) nanoparticles on the fibrillation of human serum albumin (HSA) in an in vitro mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…Literature shows that NPs have both inhibitory and stimulatory activity in the process of protein fibrillation [49][50][51]. It was observed by Bag et al [52] that graphene-based nanotherapeutics prevent the formation of HSA fibrils. However, cerium oxide NPs were found to promote protein fibrillation, as reported by Sekar et al [53].…”
Section: Srcd Measurementsmentioning
confidence: 98%
“…Literature shows that NPs have both inhibitory and stimulatory activity in the process of protein fibrillation [49][50][51]. It was observed by Bag et al [52] that graphene-based nanotherapeutics prevent the formation of HSA fibrils. However, cerium oxide NPs were found to promote protein fibrillation, as reported by Sekar et al [53].…”
Section: Srcd Measurementsmentioning
confidence: 98%
“…Images of HSA solutions when incubated alone at 65 1C displayed entangled networks of long fibrils, and these observations are found to be similar to those of earlier works. 26,52,53 Co-incubation of SAuNPs resulted in protein absorption on the nanoparticle surface and the generation of a disorganised network of protein aggregates. A further reduction of fibrillar networks and the presence of amorphous protein aggregates on gold nanosurfaces were observed in the case of QAuNP and GAuNP co-incubated HSA samples.…”
Section: Morphological Analysis Of Hsa Aggregatesmentioning
confidence: 99%
“…23 Though 37 different proteins have been reported to cause amyloid diseases, 24 human serum albumin (HSA) is extensively used as one typical a-helical (460%) protein to understand the mechanisms of the misfolding and fibrillation process. 25,26 HSA is a physiologically prolific, single chain protein containing 585 amino acids arranged in three homologous domains. 27 The literature has shown that the systematic aggregation of albumin occurs through partial misfolding of its native structure and the process has been conveniently replicated in vitro through specific conditions such as high temperature, metal ions, treatment with denaturing chemicals, and lowering of pH.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, many investigations have shown that carbon based nanomaterials such as fullerenes, carbon nanotubes, graphene and graphene oxide could be useful to inhibit the aggregation of amyloid peptides and to destroy matured brils. [37][38][39][40] The hydrophobic interaction of fullerenes gives a size-dependent destabilization of the bril structure. 41,42 It has been shown that carbon nanotubes inhibit the formation of aggregates from amyloid beta peptides (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%